2023
DOI: 10.3390/nano13060968
|View full text |Cite
|
Sign up to set email alerts
|

Combining Machine Learning and Molecular Dynamics to Predict Mechanical Properties and Microstructural Evolution of FeNiCrCoCu High-Entropy Alloys

Abstract: Compared with traditional alloys, high-entropy alloys have better mechanical properties and corrosion resistance. However, their mechanical properties and microstructural evolution behavior are unclear due to their complex composition. Machine learning has powerful data processing and analysis capabilities, that provides technical advantages for in-depth study of the mechanical properties of high-entropy alloys. Thus, we combined machine learning and molecular dynamics to predict the mechanical properties of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…These approaches are also applied in various aspects of MD simulations, 170) such as neural network potentials [54][55][56] , estimation of local atomic configuration, [171][172][173][174] and prediction of materials properties. [175][176][177][178][179][180] In particular, generative models are gaining attention in all fields as artificial intelligence tools for a new era. While there are not many examples of applying generative models to MD simulations yet, some pioneering studies have been reported.…”
Section: Application Of Machine Learning Approaches To MD Simulationmentioning
confidence: 99%
“…These approaches are also applied in various aspects of MD simulations, 170) such as neural network potentials [54][55][56] , estimation of local atomic configuration, [171][172][173][174] and prediction of materials properties. [175][176][177][178][179][180] In particular, generative models are gaining attention in all fields as artificial intelligence tools for a new era. While there are not many examples of applying generative models to MD simulations yet, some pioneering studies have been reported.…”
Section: Application Of Machine Learning Approaches To MD Simulationmentioning
confidence: 99%